Understanding and Addressing Barriers to Indigenous Learners in Business and Accounting Studies ... - Andrews, Cyril Robert (Graduate Studies, 2023)
This research addresses a significant gap in understanding the barriers Indigenous peoples face as they pursue business and accounting disciplines at the post-secondary level. Using structured interviews and content analysis, the study explored barriers and means the learners used and opined to remove or reduce those barriers. In addition, the research offers policy recommendations, including but not limited to the accounting profession, to address these challenges. The research also examines Indigenous peoples’ attitudes toward the accounting and business profession. This practical approach, with application to the accounting profession, bridges the practitioner-scholar gap noted in extant research. The findings suggest that the challenges are complex and interconnected and are deeply socialized in the fabric of Canada through societal biases and structural impediments within institutions that directly result from government policy, reserves, and residential schools. The research highlights issues not ...